Flat Panel Detector Computed Tomography-Guided Placement of External Ventricular Drains Using the BrainLAB Headband and Precalibrated Disposable Stylet Instrument: A Cadaveric Feasibility Study - Feulner, Julian; Lang, Stefan; Buder, Thomas; Struffert, Tobias; Buchfelder, Michael; Brandner, Sebastian (World Neurosurgery, 2018)
BACKGROUND: The standard freehand method for the insertion of external ventricular drains (EVDs) is associated with high rates of incorrect placement. Use of neuronavigation has been shown to reduce the rates of inaccurately positioned EVDs. We present a novel neuronavigation-based approach for EVD placement using flat panel detector computed tomography (FDCT) imaging. METHODS: Four cadaveric heads were used for neuronavigated placement of EVDs using the BrainLAB reference headband in combination with laser surface registration and the precalibrated disposable stylet. In 2 cases, conventional multislice CT imaging was performed to reference neuronavigation. In the other 2 cases, preprocedural imaging was performed with FDCT. After inserting the EVDs, all heads were examined again with the identical imaging method as used before the procedure, followed by evaluation of catheter position. RESULTS: Our data demonstrate that FDCT imaging provides adequate image quality for referencing neuronavigation and performing navigated neurosurgery. All EVDs showed an optimal position in the ipsilateral frontal horn. Use of a BrainLAB reference headband combined with laser surface registration and the precalibrated disposable stylet affords the advantage of not requiring rigid fixation in a clamp. CONCLUSIONS: Our presented method is fast, accurate, and easy to use. Furthermore, this study is the first to demonstrate that navigated neurosurgery can be performed on the basis of FDCT imaging.
EVALuna2:212791